ZMIANY W KONSUMENCKICH ZACHOWANIACH GOSPODARSTW DOMOWYCH - Grzega, Urszula (Wydział Prawa i Administracji UAM, 2001)
In the conditions of an economic transformation it is especially significant to study such elements as the behaviours of consumers and households, apart from some other key factors such as the macroeconomic indices and other economic indices as against the standard of living of the population. These behaviours are conditioned by the economy transformation and they affect the final form of the transformation as well as the extent to which the country’s accepted economic and political goals are attained. Using the results of the studies carried out from the beginning of the 1990s until 1999 the author presents the fluctuations in the behaviours of particular consumer groups towards different groups and services. One could generally conclude that more advantageous attitudes towards the market transformation are observed among those consumers who easily adapt themselves to new conditions, this group comprising young and educated people with higher salaries, often inhabiting urban areas.
CHANGES IN HOUSEHOLD CONSUMER BEHAVIOURS